(untitled) (Law and Safety, 2024)
The article is devoted to the development of a criminological model of firearms trafficking control in the context of transitional justice for Ukraine. It is established that illicit firearms trafficking lays down long-term trends of deterioration of the criminogenic situation, including in the post-war period, and in the future threatens to strengthen the functionality of organised criminal groups and a surge in violent criminal activity. The article proposes a criminological model for establishing control over firearms circulation which provides for: 1) preservation of the existing legal regime of firearms circulation for civilians until the end of the armed conflict and the legal regime of martial law; after the lifting of martial law, a balanced legalisation of civilian (short-barreled) weapons with strict control, verification and constant monitoring is required; 2) for military personnel (including those discharged from service): a) a special type of exemption from criminal liability under Articles 263 and 410 (regarding misappropriation of firearms, ammunition, explosives or other munitions) of the Criminal Code of Ukraine, subject to presentation for inspection, registration and issuance of a permit (de lege ferenda); b) obtaining a permit (de lege ferenda) for storage of firearms (in the amount of no more than one unit per person) and ammunition (in the amount of no more than 60 pieces); 3) criminal liability for violation of the conditions of the permit to keep and carry firearms. It is concluded that the enhancement of criminal liability for the illegal acquisition, transfer or sale of firearms, ammunition, explosives or explosive devices under martial law or a state of emergency is an example of excessive criminalisation of socially dangerous acts. Law enforcement agencies, by complying with the requirements on the general principles of sentencing (Article 65, paragraph 11, part 1, Article 67 of the Criminal Code of Ukraine), have sufficiently effective tools to assess and take into account the degree of social danger of various manifestations of illegal handling of weapons. The proposal is to supplement the disposition of Part 1 of Art. 263 of the Criminal Code of Ukraine with an indication of such an object of a criminal offence as a constructive part of a firearm, setting it out in the following wording: “Carrying, storing, purchasing, transferring or selling firearms or their constructive parts (except for smooth-bore hunting rifles and their constructive parts), ammunition, explosives or explosive devices without a permit provided for by law – …”.